Intercultural Competence in Extension Education: Applications of an Expert-Developed Model - John Diaz; Cody Gusto; Colby Silvert; K. S. U. Jayaratne; Lendel Narine; Sharon Couch; Celina Wille; Nozella Brown; Cintia Aguilar; Dionardo Pizaña; Kris Parker; Gayle Coon; et al. (EDIS, 2022)
This article summarizes results of a study designed to identify essential intercultural competencies for Extension professionals. Recommendations are provided for Extension administrators to inform recruitment and professional development decisions in the broader effort to provide relevant and responsive programming for multicultural audiences. Written by John Diaz, Cody Gusto, Colby Silvert, K. S. U. Jayaratne, Lendel Narine, Sharon Couch, Celina Wille, Nozella Brown, Cintia Aguilar, Dionardo Pizaña, Kris Parker, Gayle Coon, Merrianneeta Nesbitt, Laura Valencia, Dominic Ledesma, and Lupita Fabregas, and published by the UF/IFAS Department of Agricultural Education and Communication, September 2022.